2017
DOI: 10.5194/amt-2016-349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of VOC measurements made by PTR-MS, Adsorbent Tube/GC-FID-MS and DNPH-derivatization/HPLC during the Sydney Particle Study, 2012: a contribution to the assessment of uncertainty in current atmospheric VOC measurements

Abstract: Abstract. Understanding uncertainty is essential for utilizing atmospheric VOC measurements in robust ways to develop atmospheric science. This study describes an inter-comparison of the VOC data, and the derived uncertainty estimates, measured with three independent techniques (PTR-MS, AT-GC-FID and DNPH-HPLC) during the Sydney Particle Study campaigns in 2012. The compounds and compound classes compared, based on objective selection criteria from the available data, were: benzene, toluene, C8 aromatics, isop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the past decade, intercomparisons of acetaldehyde measurements between PTR-MS and various methods (including online GC-MS, DNPH-HPLC, and PTR-MS itself) were published in seven studies (Table S1). ,,,,,, The average obtained slope from the seven studies is 0.93 ± 0.29 (1.00 ± 0.26 if excluding the results by Kajos et al), suggesting reasonably good agreements in various polluted environments. However, a systematically blind intercomparison of acetaldehyde in a smog chamber suggested that acetaldehyde measurements by PTR-MS (and other techniques) may be problematic in clean background air .…”
Section: Interpretation Of Mass Spectramentioning
confidence: 62%
“…In the past decade, intercomparisons of acetaldehyde measurements between PTR-MS and various methods (including online GC-MS, DNPH-HPLC, and PTR-MS itself) were published in seven studies (Table S1). ,,,,,, The average obtained slope from the seven studies is 0.93 ± 0.29 (1.00 ± 0.26 if excluding the results by Kajos et al), suggesting reasonably good agreements in various polluted environments. However, a systematically blind intercomparison of acetaldehyde in a smog chamber suggested that acetaldehyde measurements by PTR-MS (and other techniques) may be problematic in clean background air .…”
Section: Interpretation Of Mass Spectramentioning
confidence: 62%
“…The VOC sequencer passes air samples through two different adsorbent tubes to collect the VOCs and the carbonyls respectively. These tubes were analysed at CSIRO on a gas chromatography flame ionisation detection mass spectrometer (GC-FID-MS) for VOCs (Cheng et al, 2015) and HPLC for carbonyls , which enables unambiguous species identification (this is not always provided by product ion mass numbers from the PTR-MS) at a 5, 8 or 10 h temporal resolution (Dunne et al, 2017). Unfortunately, there was a suspected leak on the VOC tube side (with very low concentrations measured), such that none of these data could be used.…”
Section: A2 Voc Sequencermentioning
confidence: 99%
“…The VOC sequencer passes air samples through two different adsorbent tubes to collect the VOCs and the carbonyls respectively. These tubes were analaysed at CSIRO on a gas chromatography flame ionisation detection/mass spectrometer (GC-FID-MS) for VOCs [Cheng, 2015] and HPLC for carbonyls [Lawson et al, 2015], which enables unambiguous species identification (which is not always provided by product ion mass numbers from the PTR-MS) at 5, 8 or 10hour temporal resolution [Dunne et al, 2017]. Unfortunately, there was a suspected leak on the VOC tube side, (with very low concentrations measured), such that none of these data could be used.…”
Section: Voc Sequencermentioning
confidence: 99%